Validitas Media Pembelajaran Interaktif JAWARA (Jelajah Warisan Budaya) berbasis Articulate Storyline Untuk Siswa Kelas V Sekolah Dasar - Alfiyatun Nikmah; Wendri Wiratsiwi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Cultural heritage is a national treasure that needs to be taught to elementary school students as an effort to instill a love for the nation's culture from an early age. However, learning about cultural heritage often lacks active student engagement, necessitating innovative, engaging, and enjoyable learning media. This study aims to determine the validity of the interactive learning media JAWARA (Jelajah Warisan Budaya) based on Articulate Storyline in social studies (IPS) learning on cultural heritage in fifth-grade elementary schools. The study used the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages; however, this study was limited to the development stage. Validity data were obtained through assessments by material experts, linguists, and media experts using a validation sheet. The results showed that the media received a validity score of 90% from the material experts, 90% from the linguists, and 95% from the media experts, categorizing it as highly valid. The overall average validity reached 91.67%. Based on these results, the JAWARA media based on Articulate Storyline is declared highly valid and suitable for use as a social studies learning medium on cultural heritage to support a more engaging and meaningful learning process in elementary schools.